Efficacy and safety analysis of montelukast sodium added on azithromycin in the treatment of Mycoplasma pneumoniae pneumonia in children - Liang, Ying; Li, Wei (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the safety and effectiveness of using montelukast sodium added on azithromycin for the treatment of pediatric Mycoplasma pneumoniae pneumonia (MPP).MethodsRetrospective analysis showed that 122 children with MPP were divided into a control group (61 cases received azithromycin treatment) and a study group (61 cases received azithromycin combined with montelukast sodium treatment) according to different treatment plans. Both groups were treated for 7 days, and lung function, lung compliance, chest CT signal, inflammatory immune status, and side effects were compared before and after treatment.ResultAfter a month of treatment, positive end expiratory pressure (PEEP) levels were lower in the research group compared to the control group’s kids, whereas forced vital capacity (FVC), tidal volume (TV), peak expiratory flow rate (PEF), pulmonary ventilation per minute (MVV), and pulmonary dynamic compliance (Cdyn) levels were greater (p < 0.05). After a month of treatment, the detection rates of lung CT signs such as bronchial wall thickening, pleural effusion (PE), ground glass density shadow (GGO), gravel sign, lymphadenopathy, consolidation of lung (LC) and bronchogenic sign in the research group were all lower than those in the control group (p < 0.05). Compared to the control group, serum levels of amyloid A (SAA), procalcitonin (PCT), lactate dehydrogenase (LDH), TOll-like receptor 4 (TLR4), and CD8 + were all lower in the research group.ConclusionAzithromycin plus montelukast sodium can effectively improve the lung function and lung compliance of children with MPP, reduce the detection rate of chest CT signs of disease symptoms, and improve the inflammatory and immune state of the body, without increasing adverse reactions, and the clinical application is safe.